2022
DOI: 10.3390/ph15050606
|View full text |Cite
|
Sign up to set email alerts
|

Elexacaftor-Tezacaftor-Ivacaftor as a Final Frontier in the Treatment of Cystic Fibrosis: Definition of the Clinical and Microbiological Implications in a Case-Control Study

Abstract: The use of modulator drugs that target the cystic fibrosis transmembrane conductance regulator (CFTR) is the final frontier in the treatment of Cystic Fibrosis (CF), a genetic multiorgan disease. F508del is the most common mutation causing defective formation and function of CFTR. Elexacaftor-tezacaftor-ivacaftor is the first triple combination of CFTR modulators. Herein, we report on a one-year case-control study that involved 26 patients with at least one F508del mutation. Patients were assigned to two simil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Migliorisi et al, using a small sample of patients (n = 26) with at least one Phe508del copy (Phe508del/Phe508del or Phe508del/MF genotypes) found out that, in one year, the ppFEV 1 of patients treated with the triple combination was augmented by 10–15 points, the number of pulmonary exacerbation was statistically significantly reduced ( p < 0.05), 77% of the cases reported a diminished SCC and 100% of the cases showed an increase in the CFQ-R RD score [ 13 ]. Studying a different group in a phase 3 trial, namely 258 patients aged ≥12 years, with Phe508del/Gating mutation or Phe508del/Residual mutation genotypes, after a 4-week run-in period where they received IVA or IVA/TEZ, respectively, Barry et al observed an increase by 3.5% (95% CI 2.2–4.7, p < 0.001) in ppFEV 1 , an absolute change in SCC by 23.1 mmol/lt (95% CI −26.1 to −20.2, p < 0.001), and an amelioration of CFQ-R RD score by 8.7 points (95% CI 5.3–12.1) through to week 8 with ELX/TEZ/IVA treatment compared to active control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Migliorisi et al, using a small sample of patients (n = 26) with at least one Phe508del copy (Phe508del/Phe508del or Phe508del/MF genotypes) found out that, in one year, the ppFEV 1 of patients treated with the triple combination was augmented by 10–15 points, the number of pulmonary exacerbation was statistically significantly reduced ( p < 0.05), 77% of the cases reported a diminished SCC and 100% of the cases showed an increase in the CFQ-R RD score [ 13 ]. Studying a different group in a phase 3 trial, namely 258 patients aged ≥12 years, with Phe508del/Gating mutation or Phe508del/Residual mutation genotypes, after a 4-week run-in period where they received IVA or IVA/TEZ, respectively, Barry et al observed an increase by 3.5% (95% CI 2.2–4.7, p < 0.001) in ppFEV 1 , an absolute change in SCC by 23.1 mmol/lt (95% CI −26.1 to −20.2, p < 0.001), and an amelioration of CFQ-R RD score by 8.7 points (95% CI 5.3–12.1) through to week 8 with ELX/TEZ/IVA treatment compared to active control.…”
Section: Resultsmentioning
confidence: 99%
“…The phase 3 study by Heijerman et al revealed that Phe508del homozygous patients ≥12 years treated with ELX/TEZ/IVA had an improvement of BMI at week 4 of 0.60 kg/m 2 (95% CI 0.41–0.79, p < 0.0001) and a mean body increase of 1.6 kg (95% CI 1–2.1, p < 0.0001) compared with TEZ/IVA group [ 11 ]. In addition, Migliorisi et al found out that patients ≥ 12 years old, with at least one Phe508del mutation treated with ELX/TEZ/IVA for one year, significantly increased their BMI, compared to the control group [ 13 ]. Furthermore, Mainz et al, in a prospective study with 107 patients, noticed that for children treated with ELX/TEZ/IVA the means for BMI-for-age z-scores increased at week 22 from −0.71 ± 0.19 to −0.29 ± 0.24 ( p = 0.002) and the mean weight from 47 ± 2.1 kg to 51.4 ± 2.3 kg ( p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case-control study, the effects of ETI therapy in 26 PwCF (F508del/MF genotype) were followed for one year [ 50 ]. The control group was composed of PwCF with mild lung disease, while the study group consisted of PwCF with advanced lung disease.…”
Section: Clinical Outcomes Of Eti Therapy In Case Reports Observation...mentioning
confidence: 99%
“…These findings were accompanied by a decreased rate of microbial colonization, with 45.3% of the samples becoming negative within one year of ETI therapy. When the CFQ-R was evaluated, all PwCF showed remarkable improvement in quality of life with a score of 100—the highest score for this questionnaire [ 50 ]. In both groups, ETI therapy resulted in an improvement of 10–15% in ppFEV 1 .…”
Section: Clinical Outcomes Of Eti Therapy In Case Reports Observation...mentioning
confidence: 99%